2020
DOI: 10.1111/pbi.13363
|View full text |Cite
|
Sign up to set email alerts
|

Increasing growth and yield by altering carbon metabolism in a transgenic leaf oil crop

Abstract: Summary Engineering high biomass plants that produce oil (triacylglycerol or TAG) in vegetative rather than seed‐related tissues could help meet our growing demand for plant oil. Several studies have already demonstrated the potential of this approach by creating transgenic crop and model plants that accumulate TAG in their leaves and stems. However, TAG synthesis may compete with other important carbon and energy reserves, including carbohydrate production, and thereby limit plant growth. The aims of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Alternatively, it may be that some technologies impose too small a sink to affect photosynthesis, especially if oils are not protected and are rapidly degraded within the leaf. Conversely, too great a sink could create excessive competition for carbon, which could hinder plant development ( Mitchell et al, 2020 ). Finally, the use of global transcription factors to enhance oil accumulation may have unintended pleiotropic effects and could impede normal cellular function ( Grimberg et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it may be that some technologies impose too small a sink to affect photosynthesis, especially if oils are not protected and are rapidly degraded within the leaf. Conversely, too great a sink could create excessive competition for carbon, which could hinder plant development ( Mitchell et al, 2020 ). Finally, the use of global transcription factors to enhance oil accumulation may have unintended pleiotropic effects and could impede normal cellular function ( Grimberg et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the cost associated with production of fuels and other bioproducts from plant biomass is relatively high, which has been a major constraint on the widespread adoption of grasses as sources of feedstock to produce biofuels or bioproducts (Hill et al , 2006; Kumar, Long and Singh, 2018). Previous work showed that C4 grasses can be genetically engineered for increased fatty acid production, resulting in biomass with high oil content (Huang, Long and Singh, 2015; Huang et al , 2016; Wang, 2016; Zale et al , 2016; Beechey-Gradwell et al , 2020; Mitchell et al , 2020; Parajuli et al , 2020), which increases their value as biofuels. Genetically engineering high-biomass grasses to accumulate valuable bioproducts that require minimal processing post-harvest is a desirable way forward, but has many challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Other proof-of-concept studies for increasing TAGs in vegetative tissues have been performed in Arabidopsis thaliana, Brachypodium distachyon, Nicotiana benthamiana, Nicotiana tabacum , sugarcane ( Saccharum spp. ), and Sorghum bicolor (Thelen and Ohlrogge, 2002; Fan, Yan and Xu, 2013; Vanhercke et al , 2013, 2019; Yang et al , 2015; Zale et al , 2016; Mitchell et al , 2020; Parajuli et al , 2020; Xu et al , 2020). For example, in engineered sugarcane, TAGs accumulated to an average of 8.0% of the dry weight of leaves and 4.3% of the dry weight of stems (Huang, Long and Singh, 2015; Zale et al , 2016; Parajuli et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During plant development, plants need to respond to developmental and environmental signals in their internal and external environments by relying on the activity of a variety of cellular components, such as for example metabolites, that trigger the appropriate metabolic responses needed for survival (Krzyzaniak et al, 2018;Matilla, 2018). It has been well described that plants have the ability to produce large amounts and a wide variety of metabolites that are important role players in their development and in response to changes in their environment (Bhatla, 2018;Bhatla & Lal, 2018;Mitchell et al, 2020), be it internal or external. These small molecules (< 1.800 Da) form the basis of crop yield and quality (Gatehouse, 2004).…”
Section: Motivation and Justification Of This Studymentioning
confidence: 99%